ASSESSMENT OF LOCAL CHROMITE SAND AS ‘GREEN’ REFRACTORY RAW MATERIALS FOR SAND CASTING APPLICATIONS IN A POST-PANDEMIC WORLD - Kabasele, Jonathan; Nyembwe, Didier (The South African Journal of Industrial Engineering, 2021)
In a post-pandemic world, health and environmental safety will become a more important issue than it was before the COVID-19 pandemic. Several fields of engineering, including the foundry industry, have already adopted health and safety measures in the workplace. The risk of pulmonary disease caused by the inhalation of fine particles of silica sand, the main moulding material used in the foundry industry, is rampant in that industry. In terms of environmental protection, the new regulatory restrictions on the disposal of used sand create the need for moulding aggregates to be more recyclable than silica. Chromite sand is an alternative refractory sand for metal casting applications, and is abundant in South Africa. The present study investigated whether this aggregate has better overall reusability than silica. The focus of this study is on the use of chromite sand in foundries as a contribution to improving health in the workplace and to reducing the environmental impact of foundry sand.